Towards a software defined network based multi-domain architecture for the internet of things - Júnior, Leonel Duque Piscalho (2020)
The current communication networks are heterogeneous, with a diversity of devices and services that challenge traditional networks, making it difficult to meet quality of service (QoS) requirements. With the advent of software-defined networks (SDN), new tools have emerged to design more flexible networks. SDN offers centralized management for data streams in distributed sensor networks. Thus, the main goal of this dissertation is to investigate a solution that meets the QoS requirements of traffic originating on Internet of Things (IoT) devices. This traffic is transmitted to the Internet in a distributed system with multiple SDN controllers. To achieve the goal, we designed a multi-controller network topology, each managed by its controller. Communication between the domains is done via an SDN traffic domain with the Open Network Operating System (ONOS) controller SDN-IP application. We also emulated a network to test QoS through OpenvSwitch queues. The goal is to create traffic priorities in a network with traditional and simulated IoT devices. According to our tests, we have been able to ensure the SDN inter-domain communication and have proven that our proposal is reactive to a topology failure. In the QoS scenario we have shown that through the insertion of OpenFlow rules, we are able to prioritize traffic and provide guarantees of quality of service. This proves that our proposal is promising for use in scenarios with multiple administrative domains.